1986
DOI: 10.1002/jsfa.2740370914
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rheological measurements on heat‐induced myosin gels: Effect of ionic strength, protein concentration and addition of adenosine triphosphate or pyrophosphate

Abstract: Myosin solutions and suspensions have been monitored during heating at pH 6.0 by using dynamic rheological measurements. The storage modulus (G'), the loss modulus ( G ) and the phase angle (6) all showed a marked dependence on ionic strength in the temperature range 25-75°C. The filamentous gels (ionic strength <0.34) displayed a temporary reduction in G' at temperatures between 50 and 60°C, presumably due to denaturation in parts of the rod portion of the myosin molecule. In the same temperature region the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
97
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 26 publications
(1 reference statement)
13
97
0
Order By: Relevance
“…G' showed a shoulder transition between 47 and 52°C, increased abruptly at higher temperatures and began to level off at 72°C. The change in G' of non-oxidised myosin essentially agreed with the results reported by Egelandsdal et al 19 These authors also suggested that the G' shoulder was due to denaturation of the rod portion of the myosin molecule. The viscoelastic pattern of myosin was altered after incubation with the oxidants.…”
Section: Gelationsupporting
confidence: 87%
“…G' showed a shoulder transition between 47 and 52°C, increased abruptly at higher temperatures and began to level off at 72°C. The change in G' of non-oxidised myosin essentially agreed with the results reported by Egelandsdal et al 19 These authors also suggested that the G' shoulder was due to denaturation of the rod portion of the myosin molecule. The viscoelastic pattern of myosin was altered after incubation with the oxidants.…”
Section: Gelationsupporting
confidence: 87%
“…On subsequent heating to 80°C, the G′ rose steadily, as has also been shown previously (Carballo, Cofrades, Fernández-Martín, & Jiménez-Colmenero, 2001). The initial increase in G′ trend indicated the onset of gelation or the formation of the preliminary elastic protein network, which was probably due to the unfolding and cross-linking of heavy meromyosin (Egelandsdal, Fretheim, & Samejima, 1986;Jiang & Xiong, 2013). The temporary decrease in G′ was attributed to the denaturation of the myosin tails, which involved the disentanglement of noncovalent, short-term intermolecular interactions to increase the mobility of muscle proteins (Liu, Zhao, Xiong, Xie, & Qin, 2008;Xiong, 1997).…”
Section: Storage Modulus (G′)mentioning
confidence: 99%
“…Two main transition temperatures (around 45°C and 60°C) were found by using differential plots of G' against temperature (data not shown). These values are slightly different from those reported by Ishioroshi et al 6) This may have have been due to a difference in the measuring conditions and the methods, as Egelandsdal et al 30,31) have pointed out that the rheological parameters of myosin showed marked dependence on the ionic strength, protein concentration, heating rate and so on. Samejima et al 32 ) have reported that two transition temperatures of 43°C and 55°C were respectively due to the aggregation of the globular head portion and unfolding of the tail portion of the myosin molecules during heating.…”
Section: Dynamic Rheological Measurementsmentioning
confidence: 58%